Flight Performance of a VTOL Version of a Transport Blended Wing-Body UAV - Saifuddin, Che Noureen Sabrina; Abdul Muta'ali, Atikah Basyirah; Mohd Nasir, Rizal Effendy (International Journal of Integrated Engineering, 2025)
The blended wing-body (BWB) UAV with vertical take-off and landing (VTOL) capabilities has garnered attention in aviation due to its advancements and advantages, such as noise reduction and safety features. This study analyses BWB UAV VTOL flight performance and mission capabilities. The evaluation involves conceptual design, theoretical calculations, and data analysis to assess parameters such as range, endurance, weight, manoeuvrability, and more. Furthermore, mission profile analysis is used for surveillance scenarios and offers insights into the UAV’s performance in these operational environments. Microsoft Excel is the main tool used in this research for calculations, simulations, and data analysis. Using a spreadsheet, this method computes critical performance metrics according to the mission requirements, operational parameters, and design specifications of the UAV. The study’s findings provide important insight into the BWB UAV VTOL prototype’s flight characteristics and mission capabilities. These results point to the aircraft’s ideal operating conditions and assist in identifying any potential drawbacks or performance limitations that may vary as further study proceeds. Microsoft Excel provides a useful and approachable way to evaluate UAV VTOL performance. It enables fast updates and modifications to meet changing mission requirements and design iterations. Other than that, a thorough examination of the flight characteristics and mission profile of the BWB UAV VTOL prototype brings this study to a close. It offers insightful information that can be used to improve design, schedule operations, and predict performance in the field of aerial transportation and other pertinent applications.